THE ESSENCE OF INSTITUTIONAL SUPPORT FOR INNOVATIVE DEVELOPMENT - HRYB, Serhiy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the problems of managing innovative development in Ukraine. It considers the significance of innovative development of the domestic economy against the backdrop of political and economic crisis and concludes that there are serious obstacles and challenges, especially in the context of the ongoing war with the Russian Federation. The innovative activity of Ukrainian industrial enterprises in recent years is analyzed, and the main trends for change are identified. It was determined that there is an increase in innovation-active domestic industrial enterprises and an increase in the volume of innovative products being introduced. This positive trend shows the willingness of business structures to respond flexibly to technical and technological challenges and to update their activities in accordance with the requirements of scientific and technological progress. The study also shows that innovative activity is implemented only in a small number of industrial enterprises. Conclusions are made regarding the absence of an effective organizational and economic mechanism to promote the innovative development of the domestic economy.The essence of the concept of “institutions” is explored and their main types are considered. The feasibility of introducing a comprehensive approach to managing innovative development based on its institutional support is substantiated. The main problems of institutional support in Ukraine are considered, which include the existence of complex bureaucratic procedures for obtaining permits and licenses, insufficient funding, and tax incentives. The main directions for the formation of effective institutional support for innovative development are identified. This includes improving the legal regulation system, forming a strategy for innovative development, improving the tax and credit-financial system, taking into account international experience, and building the necessary infrastructure facilities, etc.
Keywords: innovative development; institutions; innovative projects; institutional support; legal system; financial and credit sphere